Precision Isolation of Circulating Leukemia Cells in Chronic Myelogenous Leukemia Patients Using a Novel Microfluidic Device and Its Clinical Applications. - Ouyang, Dongfang; Ye, Ningxin; Yang, Kun; Wang, Yiyang; Hu, Lina; Chao, Shuen; Toner, Mehmet; Li, Yonghua (Cancers, 2023)
Simple Summary: Chronic Myelogenous Leukemia (CML) is a common blood cancer that involves the uncontrolled growth of certain blood cells. Treating this disease effectively requires doctors to detect and eliminate even the smallest traces of cancer cells, a process known as managing minimal residual disease. However, current methods to find these cells, like bone marrow tests, are not only uncomfortable for patients but also have some drawbacks, such as missing cancer cells. This study introduces an innovative, less invasive approach using a microfluidic chip. This chip works by analyzing a patient's blood sample to find and measure the number of leukemia cells. We tested this device on 56 patients with CML and found that it could successfully identify these cancer cells in blood, with a high accuracy rate. This new method is promising because it is less invasive and more precise, making it easier to monitor how well a patient's treatment is working and to make better treatment decisions. This advancement could significantly improve the care and outcomes of people with CML, making a real difference in their lives. Chronic Myelogenous Leukemia (CML) is a prevalent hematologic malignancy characterized by the malignant transformation of myeloid cells and their proliferation in the peripheral blood. The management of CML poses significant challenges, particularly in detecting and eradicating minimal residual disease, which is crucial for preventing relapse and improving survival outcomes. Traditional minimal residual disease detection methods, such as bone marrow aspiration, are invasive and have limitations which include the potential for sampling errors and false negatives. This study introduces a novel label-free microfluidic chip designed for the segregation and recovery of circulating leukemia cells, offering a non-invasive liquid biopsy approach with potential applications in precision medicine. Over July 2021 to October 2023, we recruited 56 CML patients across various disease stages and collected blood samples for analysis using our microfluidic device. The device demonstrated high efficacy in isolating circulating leukemia cells, with an optimal capture efficiency of 78% at a sample flow rate of 3 mL/h. Our results indicate that the microfluidic device can efficiently segregate and quantify circulating leukemia cells, providing a detailed understanding of CML progression and treatment response. The significant reduction in circulating leukemia cell counts in patients in complete remission highlights the device's potential in monitoring treatment efficacy. Furthermore, the device's sensitivity in detecting minimal residual disease could offer a more reliable prognostic tool for therapeutic decision-making in CML management.